2022
DOI: 10.1039/d2ja00245k
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution continuum source graphite furnace molecular absorption spectrometry for the monitoring of Sr isotopes via SrF formation: a case study

Abstract: High-resolution continuous source graphite furnace molecular absorption spectrometry (HR CS GFMAS) can provide isotopic information under certain conditions, thus broadening its field of application. However, up to date, only elements...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…This strategy had provided good results in a previous work of the group for promoting the SrF molecule and performing Sr isotope ratio determinations, although this approach also requires careful optimization. 30 Briefly, the protocol for fluorination in the gas phase consists of filling the graphite tube with the reactive gas (Ar/CH 3 F in this case) at the end of the pyrolysis step, then stopping the inner gas flow in the furnace for reducing the diffusion rate of gases out of the furnace and subsequently heating the system to vaporize/atomize the analyte in an atmosphere rich in the reactive gas, where the target fluoride molecule can be formed. For the particular case of boron, the presence of the fluorinating agent in the gas phase during this step should promote B vaporization from the sampling platform at a lower temperature than in its absence (probably as a fluoride species), even if very refractory carbides would have been formed.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This strategy had provided good results in a previous work of the group for promoting the SrF molecule and performing Sr isotope ratio determinations, although this approach also requires careful optimization. 30 Briefly, the protocol for fluorination in the gas phase consists of filling the graphite tube with the reactive gas (Ar/CH 3 F in this case) at the end of the pyrolysis step, then stopping the inner gas flow in the furnace for reducing the diffusion rate of gases out of the furnace and subsequently heating the system to vaporize/atomize the analyte in an atmosphere rich in the reactive gas, where the target fluoride molecule can be formed. For the particular case of boron, the presence of the fluorinating agent in the gas phase during this step should promote B vaporization from the sampling platform at a lower temperature than in its absence (probably as a fluoride species), even if very refractory carbides would have been formed.…”
Section: Resultsmentioning
confidence: 99%
“…To test if these assumptions were true, a preliminary temperature program based on the results shown in ref. 30 was tested. Again, 10 μL of a 1000 mg L −1 B standard solution were introduced in the graphite furnace, to maximize the probability to obtain an analytical signal.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Bazo et al 65 demonstrated the possibility of using a CS-AAS instrument as a molecular absorption spectrometer for determining Sr isotope ratios in spiked tap water. Using an Ar/CH 3 F gas mixture as the fluorinating agent and an Ar/H 2 mixture as a purge gas, Sr isotopes could be detected as SrF molecules at 630.27 nm.…”
Section: Water Analysismentioning
confidence: 99%